PENERAPAN TOTAL PRODUCTIVE MAINTENANCE DALAM EVALUASI KINERJA PERAWATAN ALAT BERAT EXCAVATOR MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS - Miranti Putry; Toto Sudianto; Firyaliza Dwi Putri (Universitas Dirgantara Marsekal Suryadarma, 2026)
In construction projects, productivity, operational continuity, and maintenance costs are significantly influenced by heavy equipment reliability. Since excavators are among the most frequently used machines, efficient maintenance management is crucial to reduce downtime and improve operational effectiveness. This study uses Total Productive Maintenance (TPM) techniques and Overall Equipment Effectiveness (OEE) evaluation to assess excavator maintenance performance and develop appropriate maintenance improvement solutions. Using operational and maintenance data collected from an excavator operated by a heavy equipment rental company over a four-month observation period, a quantitative case study was conducted. Three key indicators were used to assess maintenance performance: availability, performance, and quality. These indicators were combined to estimate the OEE value. Priorities for maintenance improvement were then determined using this analysis. The study found that equipment availability increased from 94.19% to 97.32%, indicating a decrease in downtime due to maintenance activities. However, the average Quality Ratio was approximately 87%, while equipment performance remained relatively stable at approximately 72%. Therefore, the OEE value was below the acceptable operational threshold, ranging from 58.06% to 61.44%. These results indicate that although OEE has been successfully increased through improvement efforts, operational efficiency and process quality still need to be significantly improved. To improve equipment reliability and operational efficiency, recommended strategies include autonomous maintenance, planned maintenance, quality maintenance, and operator training.